Toward a Framework for Financial Stability - Lindgren, Carl-Johan (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1998)
This study outlines the broad principles and characteristics of stable and sound financial systems, to facilitate IMF sruveillance over banking sector issues of macroeconomic significance and to contribute the general international effort to reduce the likelihood and diminish the intensity of future financial sector crises.